IMPLEMENTASI METODE NADZOM WUJUD, QIDAM, BAQA DALAM PENDIDIKAN TAUHID BAGI ANAK USIA DINI (STUDI KASUS PADA ANAK USIA 5-6 TAHUN DI PAUD IBNU UMAR) - Ilham Ramadhan; Ema Marhamah; Hendar Suhendar (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
Tauhid education in early childhood, especially in educational institutions for children, is by introducing the qualities that exist in Allah from an early age. Through nadzom wujud, qidam, baqa, children will understand the nature of Allah, which means existing, previous and eternal, and children can apply it to everyday life. Through this method, learning will be more interactive and conducive to children being taught abstract things but will understand and believe in them wholeheartedly. This research aims to find out how monotheism education is implemented through nadzom wujud, qidam, baqa in PAUD Ibnu Umar. Based on the problem of children's low knowledge regarding Tauhid education, it encouraged researchers to conduct this research which aims to apply knowledge and understanding about tauhid education. This research uses qualitative research, using data collection techniques, namely observation, interviews, document study and triangulation. Based on the results of the research, it shows that: (1) The implementation of the nadzom wujud, qidam, baqa method for tauhid education for children aged 5-6 years at Ibnu Umar PAUD cannot be separated from the daily learning implementation plan (modul ajar), as for the nadzom wujud, qidam, baqa learning planning stated in the RPPH are the learning steps and time allocation used. Second, the implementation of this method activity, which was initially limited to nadzom, was developed with an understanding of the meaning and application in everyday life. Third, the evaluation of learning outcomes looked very good with the increase in children's learning achievements. Teachers understanding of this method is proven by a systematic and well-planned learning flow and increasing and developing student evaluation results. This method is proven to be effective by referring to the implementation of learning and teacher understanding.